The Influence of Human Capital Management and Organizational Agility on Hospital Service Quality through Perceptions of Organizational Support - Mikaria Gultom; Setyo Ryanto; Mafizatun Nurhayati; Singmin Johanes Lo (Dinasti International Journal of Education Management And Social Science, 2024)
The aim of this research is to examine the influence of human capital management (HCM) and organizational agility (AO) on the quality of group private hospital services, which is mediated by perceived organizational support (PDO). The population in this study was the accreditation team that was active in the preparation, implementation, and follow-up of the results of the hospital accreditation assessment, totaling 656 people, and the target sample taken using the stratified random sampling method was 253 people. This research uses path modeling analysis techniques with PLS tools. Based on the tests carried out, it was found that human capital management influences the quality of hospital services, organizational agility influences the quality of hospital services, perceived organizational support influences the quality of hospital services, and perceived organizational support mediates the influence of human capital management and perceived organizational support on the quality of hospital services.